UPAYA GURU DALAM PENDIDIKAN AKHLAK ANAK TERHADAP DAMPAK MEDIA SOSIAL DI SMP NEGERI 10 BANJARBARU - Maya, Maya; Qomariyah, Nurul (Program Studi PAI STAI Al Falah Banjarbaru, 2024)
Abstract: This study discusses Teacher Efforts in Children's Moral Education on the Impact of Social Media at SMP Negeri 10 Banjarbaru. The formulation of the problem in this study is How are the efforts of teachers in children's moral education on the impact of social media at SMPN 10 Banjarbaru and What are the inhibiting and supporting factors of teacher efforts in children's moral education on the impact of social media at SMPN 10 Banjarbaru. The subjects in this study were 3 Islamic religious education teachers, while the objects in this study were Teacher Efforts in Children's Moral Education on the Impact of Social Media at SMP Negeri 10 Banjarbaru and supporting and inhibiting factors. In data collection here using observation, interview, and documentation techniques, while for data processing techniques carried out with data classification, editing, and data interpretation, then analyzed with qualitative descriptive analysis and conclusions drawn inductively. The methods used by teachers by PAI teachers to overcome the impact of social media are the exemplary method, advice and sanctions. and by providing reinforcement to students. The supporting and inhibiting factors are: teachers, students, environment, family, and facilities and infrastructure. Based on the results of the study, it is known that the exemplary method, advice and sanctions carried out by teachers have been running and the results are good. This can be seen from students who say hello when they meet teachers, greet friends well, students who are diligent in praying Dhuhur in congregation, reading Yasiin orderly and sanctions can be seen from the absence of students who dare to bring cellphones to school without the teacher's permission. Keywords: Morals, Social Media, Teacher Efforts. Abstrak: Penelitian ini membahas tentang Upaya Guru dalam Pendidikan Akhlak Anak terhadap dampak Media Sosial di SMP Negeri 10 Banjarbaru. Rumusan masalah dalam peneliti ini adalah Bagaimana upaya guru dalam pendidikan akhlak anak terhadap dampak media sosial di SMPN 10 Banjarbaru serta Apa saja faktor penghambat dan pendukung upaya guru dalam pendidikan akhlak anak terhadap dampak media sosial di SMPN 10 Banjarbaru. Subjek dalam peneliti ini adalah 3 Guru pendidikan agama Islam, sedangkan obyek dalam penelitian ini adalah Upaya Guru dalam Pendidikan akhlak anak terhadap dampak media social di SMP Negeri 10 Banjarbaru serta faktor mendukung dan menghambat. Dalam penggalian data disini menggunakan teknik observasi, wawancara, dan dokumentasi adapun untuk teknik pengolahan data dilakukan dengan klasifikasi data, editing, dan interpretasi data, selanjutnya dianalisis dengan analisis deskriptif kualitatif dan ditarik simpulan secara induktif. Adapun metode yang digunakan guru oleh guru PAI untuk mengatasi dampak media sosial adalah metode keteladanan, nasehat dan sanksi.dan dengan memberikan penguatan kepada siswa. Adapun faktor pendukung dan penghambat yaitu: guru, siswa, lingkungan, keluarga, serta Sarana dan prasaran. Berdasarkan hasil penelitian diketahui metode keteladahan, nasehat dan sanksi yang dilakukan oleh guru sudah berjalan dan hasilnya baik. Hal ini bisa dilihat dari siswa yang mengucapkan salam ketika bertemu guru, menyapa teman dengan baik, siswa yang sudah rajin sholat zuhur berjamaah, membaca yasiin dengan tertib serta sanksi terlihat dari tidak adanya siswa yang berani membawa hp kesekolah tanpa seizin guru. Kata Kunci: Akhlak, Media Sosial, Upaya Guru.